Perbaikan Program Maintenance Dengan Pendekatan Reliability Centered Maintenance (Rcm) Untuk Mengurangi Aircraft On Grounded (Aog) Di Pt. Nusantara Buana Air (Jurnal Inovisi (Teknik Industri), 2013)
AbstractPT. Nusantara Buana Air (NBA) is a company engasged in yhe field of aviation support and serves charter flight between remote island with a minimum 800 meter runway hard landing. In order to remain able to grow in the fierce competetion, NBA must be able to reduce the time delay and Aircraft on Grounded (AOG). This research aims to reduce AOG by applying Reliability Centered Maintenance compenents. Â RCM is a maintenance approach that combines preventive maintenace practices and strategies (PM) and corective maintenace (CM) to maximize the life (life time) and the function of system at minimal cost. Â The biggest factor causing AOG is Program Maintenance- Inspection C6 which takes 75 days. This study concludes AOG may be reduced to 40 days through the determination of the root cause and make improvements in the examination C6 with RCM approach.